Kombinace. - Timár, Katalin; Merta, Dan; Prague Castle, Prague (Praha : Správa Prazského hradu, 1996)
El-Hassan, Róza ; Veszely, Beáta ; Lakner, Antal ; Csörgo, Attila ; Beöthy, Balázs ; Menesi, Attila ; Várnai, Gyula
The Ball-Game Hall in the Royal Garden of the Prague Castle from 10 July until 25 August 1996
kunstcatalogus